Multidisciplinary administrative-professional-technical interventions to optimize antibiotic use and reduce resistance in a tertiary general hospital - Han, Jingjing; Shen, Meiyu; Rao, Yan (Frontiers in Pharmacology, 2025)
IntroductionAntimicrobial stewardship (AMS) is a cornerstone of global antimicrobial resistance (AMR) strategies. However, substantial differences exist in AMS implementation approaches and effectiveness among medical institutions across nations and regions. This study aimed to evaluate strategies focused on antimicrobial usage and AMR in a tertiary general hospital.MethodsThis study was conducted in two phases: the baseline phase (January to June in 2023) and the intervention phase (July 2023 to June 2024). During the intervention phase, an innovative AMS strategy integrating multidisciplinary administrative, professional, and technical interventions was implemented to reduce antibiotic use and control antimicrobial resistance.ResultsAfter intervention, the antimicrobial usage rate among inpatients decreased from 56.01% to 52.71% (P < 0.001). The antibiotic use density (AUD) decreased from 50.15 to 35.76 Defined Daily Doses (DDDs) per 100 patient-days (P < 0.001). The antimicrobial usage rates and AUD dropped significantly in medical, surgical, obstetrics and gynecology wards. Moreover, the intervention effect in pediatric wards displayed complex seasonal variation. The AUD for most antibiotic classes was significantly lower after the intervention. The detection rates of carbapenem-resistant Klebsiella pneumoniae and Acinetobacter baumannii decreased from 26.00% to 17.53% and 89.58% to 62.93%, respectively.ConclusionThe findings indicate that a multifaceted AMS strategy, integrating multidisciplinary administrative, professional, and technical interventions, offers a potentially effective strategy for reducing antimicrobial usage and combating AMR in the tertiary general hospital.